A multiplex RPA coupled with CRISPR-Cas12a system for rapid and cost-effective identification of carbapenem-resistant Acinetobacter baumannii - Zhou, Zihan; Liang, Lina; Liao, Chuan; Pan, Lele; Wang, Chunfang; Ma, Jiangmei; Yi, Xueli; Tan, Meiying; Li, Xuebin; Wei, Guijiang (Frontiers in Microbiology, 2024)
Carbapenem-resistant Acinetobacter baumannii (CRAB) poses a severe nosocomial threat, prompting a need for efficient detection methods. Traditional approaches, relying on bacterial culture and PCR, are time-consuming and cumbersome. Leveraging the CRISPR-based gene editing system, we integrated recombinase polymerase amplification (RPA) and CRISPR-Cas12a to swiftly diagnose CRAB-associated genes, OXA-51 and OXA-23. This multiplex RPA-CRISPR-Cas12a system eliminates bulky instruments, ensuring a simplified UV lamp-based outcome interpretation.Operating at 37°C to 40°C, the entire process achieves CRAB diagnosis within 90 minutes. Detection limits for OXA-51 and OXA-23 genes are 1.3×10 -6 ng/μL, exhibiting exclusive CRAB detection without cross-reactivity to common pathogens. Notably, the platform shows 100% concordance with PCR when testing 30 clinical Acinetobacter baumannii strains. In conclusion, our multiplex RPA coupled with the CRISPR-Cas12a system provides a fast and sensitive CRAB detection method, overcoming limitations of traditional approaches and holding promise for efficient point-of-care testing.